ANALISIS KINERJA PEGAWAI DI BADAN KEPEGAWAIAN, PENDIDIKAN, DAN PELATIHAN DAERAH (BKPPD) KOTA SURAKARTA - Tri Wulandari; Wiedy Murtini; Hery Sawiji (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2020)
Abstract This study aim to determine the performance of employees, the obstacles faced by employees and efforts to improve the performance of employees at the Regional Personnel, Education, and Training Agency of Surakarta City. The research is a descriptive qualitative method with a case study approach. The data used are primary and secondary data. Sources of data come from informants, places/events, and documents. Sampling techniques using purposive sampling techniques and snowball sampling. Data validation was carried out by: (1)Credibility, (2)Transferability, (3)Dependability, and (4)Confirmability. The data analysis technique was carried out by: (1)Data collection; (2)Data Reduction; (3)Presentation of Data; (4)Drawing conclusions. The research procedures adopted by researchers included: (1)Proposal and Licensing Preparation Stage; (2)Data Collection Stage; (3)Initial Data Analysis Phase; (4)Final Data Analysis Phase; (5)Report Writing Stage and Report Reproduction. The results shows (1)Service orientation; (2)Commitment; (3)Work Initiatives; (4)Cooperation; (5)Leadership. Barriers to employee performance include: (a) Time Management; (b) Limited Human Resources; (c) Infrastructure; (d) Educational Background. Efforts have made to improve employee performance, among others, prioritizing more important work, to support and assistance between employees, providing training to improve employee competencies, and maintaining and improving available infrastructure. Keywords : performance, employees, performance assessment, work behavior